2008
DOI: 10.1007/s00024-007-0281-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Diffuse CO2 Emission and Relation to Seismic Activity in and around El Hierro, Canary Islands

Abstract: Significant changes in the diffuse emission of carbon dioxide were recorded in a geochemical station located at El Hierro, Canary Islands, before the occurrence of several seismic events during 2004. Two precursory CO 2 efflux increases started thirteen and nine days before two seismic events of magnitude 2.3 and 1.7, which took place near El Hierro Island, Canary Islands, on March 23 and April 15, reaching a maximun value of 51.1 and 46.2 g m -2 d -1 , respectively, five and eight days before the two seismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Padrón et al . [] also recognized diurnal and semidiurnal fluctuations in the gas flux assessed in 2004 for a station located on El Hierro Island (Canary Islands). These above mentioned studies only suggested that CO 2 efflux periodicities are related to the air temperature and barometric pressure cycles without any attempts to model these phenomena.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Padrón et al . [] also recognized diurnal and semidiurnal fluctuations in the gas flux assessed in 2004 for a station located on El Hierro Island (Canary Islands). These above mentioned studies only suggested that CO 2 efflux periodicities are related to the air temperature and barometric pressure cycles without any attempts to model these phenomena.…”
Section: Discussionmentioning
confidence: 96%
“…In some studies cyclic variations in 222 Rn time series have also been identified, both in the air [e.g., Groves‐Kirkby et al ., ; Pinault and Baubron , ; Richon et al ., ; Rigby and La Pointe , ; Robinson et al ., ; Steinitz et al ., ] and in the soil [ Aumento , ; Cigolini et al ., ; Perrier and Girault , ; Richon et al ., , ]. However, despite the recognized influence of environmental conditions on the CO 2 efflux behavior, there are only a few studies in the literature that have reported daily variations in soil CO 2 emitted from volcanic/hydrothermal areas [ Granieri et al ., ; Padrón et al ., ; Hernández et al ., ]. Recently, Rinaldi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the 3.7-year periodicity was relevant in both the atmospheric CO2 growth rate and in the seismic-moment release rate spectra, as well as other periodicities such as the 2.5-year spectral peaks (see Figure 5B,C). Then, residuals are subjected also to coherence analysis [60] to find out more Figure 5. (A) FFT spectra of the de-trended time series for: Anthropogenic CO 2 emissions; (B) the global seismic-moment release rate; (C) and the atmospheric CO 2 growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Piezonuclear can also be put into correlation with the increase in seismic activity that has occurred over the last century [58]. Very recent evidence has shown CO 2 emissions in correspondence with seismic activity [59]: significant changes in the diffuse emission of carbon dioxide were recorded in a geochemical station at El Hierro, in the Canary Islands, before the occurrence of several seismic events during the year 2004. Appreciable precursory CO 2 emissions were observed to start before seismic events of relevant magnitude and to reach their maximum values some days before the earthquakes [59].…”
Section: Geochemical Evidence Of Piezonuclear Reactions In the Evolutmentioning
confidence: 99%